Qualitative Analysis for Phytochemicals of Selected Medicinal Plants from Gilgit-Baltistan, Pakistan - Ismail, Muhammad; Ali, Sajjad; Ali, Iftikhar; Shaheen, Rubina; Murtaza, Ghulam (Asian Journal of Chemistry, 2017)
Three medicinal plants from Gilgit-Baltistan region of Pakistan were selected for detailed qualitative analyses to identify different phytochemicals. The leaves and stems of these medicinal plants were used during this study. For each plant sample the methanolic extracts were initially obtained which were further fractionated into n-hexane, dichloromethane and water fractions by solvent-solvent extraction method. All these fractions were qualitatively analyzed for alkaloids, flavonoids, steroids, tannins, saponins, sterols, phenols, quinones and coumarins by using standard methods for analysis. Among three selected plant species, alkaloids were present in all extracts with equal positive results except hexanes extract of A. brevifolia, while flavonoids were present in all extracts of A. brevifolia and absent in all other extracts of C. botrys and S. surrattense (except water extract). The results also indicated that the steroids were present in only water extracts and tannins were present in both dichloromethane and water fractions of all three-plant species in this study. The results showed that the phytochemicals such as saponins, quinones and coumarins were present in one or the other fractions of A. brevifolia, C. botrys and S. surrattense while sterols were present in A. brevifolia and C. botrys and phenols in only dichloromethane fraction of S. surrattense. In present study, we observed that the water extract in comparison to other types of extracts gave the highest positive results with different reagents for the qualitative determination of phytochemicals, similarly n-hexane extract gave mostly negative results and dichloromethane extract shows moderate results. The qualitative analysis showed that the alkaloids were the major phytochemical constituents present in highest concentration in all plant extracts with positive results while flavonoids, sterols and phenols were absent in majority of different fractions.